2020
DOI: 10.1155/2020/3547491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative HbA1c Levels on the Postoperative Outcomes of Coronary Artery Disease Surgical Treatment in Patients with Diabetes Mellitus and Nondiabetic Patients: A Systematic Review and Meta-Analysis

Abstract: Aims. To investigate the effect of preoperative HbA1c levels on the postoperative outcomes of coronary artery disease surgery in diabetic and nondiabetic patients. Methods and Results. The MEDLINE (via PubMed), Cochrane Library, Web of Science, Embase, Wanfang Data, China National Knowledge Infrastructure (CNKI), and Chinese Biology Medicine (CBM) databases were used to search the effects of different preoperative HbA1c levels on the postoperative outcomes of coronary artery disease surgical treatment in diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
2
31
0
1
Order By: Relevance
“…Many patients requiring cardiac surgery have a high glycemic load, which is known to increase the risk of adverse postoperative outcomes. 1 Yet, precise estimates associated with a milieu of clinically relevant short-and long-term postoperative outcomes using varying degrees of glycemic thresholds are not available.…”
Section: Scott Kehler Phdmentioning
confidence: 99%
“…Many patients requiring cardiac surgery have a high glycemic load, which is known to increase the risk of adverse postoperative outcomes. 1 Yet, precise estimates associated with a milieu of clinically relevant short-and long-term postoperative outcomes using varying degrees of glycemic thresholds are not available.…”
Section: Scott Kehler Phdmentioning
confidence: 99%
“…A prospective study has reported an association of acute renal failure as a complication following CABG 39 . Wang et al 40 conducted a meta‐analysis of nine studies, and they have found that poor control of blood sugar is associated with higher risks of renal failure after cardiac surgery (OR, 1.63; 95% CI, 1.13‐2.33). Similarly, Halkos et al 41 showed an increased risk of renal failure (OR, 2.1) following elective CABG at a single academic center.…”
Section: Pharmacology Of Antidiabeticsmentioning
confidence: 99%
“…27 A prospective study has reported an association of acute renal failure as a complication following CABG. 39 Wang et al 40 43 Due to the limited sample size of one hospital's patient population, whether these results can be generalized, or could other hospital trusts find more success in LOS reduction in postoperative patients remains to be seen. Other studies have shown that poor control of blood sugar levels is associated with and correlated to longer hospital stay than those with optimal glycemic control (mean LOS of 7.5 days vs 6.5 days), or a 1.08-day mean increase in LOS.…”
Section: Effect Of Newer Antidiabetics On Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a larger and more recent meta-analysis (n=5,381) conducted by Wang et al showed that there was no significant difference in stroke incidence between diabetic patients with lower preoperative HbA1c levels and those with higher preoperative HbA1c levels after CABG and PCI (OR 1.49, 95% CI 0.94-2.37, p = 0.37, andI 2 = 8%) 48 . Higher HbA1c levels were defined as preoperative HbA1c [?]…”
Section: Hba1c and Cerebrovascular Accidentmentioning
confidence: 97%